2019
DOI: 10.1111/apha.13325
|View full text |Cite
|
Sign up to set email alerts
|

AKAP12 deficiency impairs VEGF‐induced endothelial cell migration and sprouting

Abstract: Aim Protein kinase (PK) A anchoring protein (AKAP) 12 is a scaffolding protein that anchors PKA to compartmentalize cyclic AMP signalling. This study assessed the consequences of the downregulation or deletion of AKAP12 on endothelial cell migration and angiogenesis. Methods The consequences of siRNA‐mediated downregulation AKAP12 were studied in primary cultures of human endothelial cells as well as in endothelial cells and retinas from wild‐type versus AKAP12−/− mice. Molecular interactions were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 70 publications
1
30
0
Order By: Relevance
“…CHD and specifically right ventricular outlet obstruction are present in a fraction of the cases (39). The results also suggested other constrained genes not previously identified, with evidence that supports a role in the VEGF pathway or other complementary mechanisms for TOF, from human (e.g., AKAP12 ), mouse (e.g., EPN1 , ATF2 ) or both ( PKD1 ) (Table 3) derived gene-sets (4044).…”
Section: Discussionsupporting
confidence: 68%
“…CHD and specifically right ventricular outlet obstruction are present in a fraction of the cases (39). The results also suggested other constrained genes not previously identified, with evidence that supports a role in the VEGF pathway or other complementary mechanisms for TOF, from human (e.g., AKAP12 ), mouse (e.g., EPN1 , ATF2 ) or both ( PKD1 ) (Table 3) derived gene-sets (4044).…”
Section: Discussionsupporting
confidence: 68%
“…For instance, studies have shown that the pan-cellular increases in cAMP caused by agents that activate all transmembrane adenylyl cyclases, including agents such as forskolin, or which inhibit all cellular cAMP-hydrolyzing phosphodiesterases (PDEs), like isobutyl-methyl-xanthine (IBMX), consistently reduce ASMC migration [1]. For these reasons, cAMP-elevating agents have long been seen as attractive agents through which to reduce ASMC migration in several conditions, including in-stent restenosis, where PDE4 inhibition reduces neointima formation and inhibits vascular cell adhesion molecule 1 (VCAM-1) expression and histone methylation in an exchange protein activated by cAMP (EPAC)-dependent manner [2,3] Interestingly, notwithstanding the observation that increased cAMP signaling results in reduced levels of ASMC migration, when the numerous steps involved in coordinating cellular migration are studied individually, it is found that they are equally likely to be inhibited or promoted [1,[4][5][6]. For instance, while increased protein kinase A (PKA) activity reduces overall cellular migration, PKA activation promotes, rather than inhibits, the formation of cellular protrusions at the cellular front, a critical early step in polarizing cells for migration [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Acta Physiologica, Benz et al study the role of one important protein in the cyclic AMP signalling pathway, the A-kinase anchoring (AKAP)12. 1 The downstream effects stemming from cAMP release are tightly controlled and activate a profusion of signalling pathways. However, many of these different processes function with largely the same major constituent proteins, including adenylate cyclases, kinases, phosphatases and phosphodiesterases.…”
Section: E D I T O R I a L The Role Of Akap12 In Coordination Of Vegfmentioning
confidence: 99%
“…In this issue of Acta Physiologica, Benz and colleagues present their findings on the role AKAP12 plays in endothelial cell migration and angiogenesis. 1 Through a combination of biochemical, proteomic and imaging techniques, the authors detail how AKAP12 expression in migrating endothelial cells may coordinate the integration of angiogenic stimuli and PKA activity-induced changes in actin dynamics that drive cell movement. In this work, Benz and co-workers addressed both the differential expression of AKAP12 in migrating cells, and its functional role in coordinating signal integration that helps to drive endothelial cell motility.…”
Section: E D I T O R I a L The Role Of Akap12 In Coordination Of Vegfmentioning
confidence: 99%
See 1 more Smart Citation